Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas Xc SMAN 1 Bungin - Ramadhan, Puji Laila; Anwar, Muhammad; Danial, Muhammad (Chemistry Education Review (CER), 2024)
This research is a Classroom Action Research (CAR) is aim to determine how to implement it the steps system the implementation of NHT learning models to improve student learning activitie and learning outcomes in class Xc SMAN 1 Bungin, Kab. Enrekang. This study was conducted by two cycles. The steps NHT implemente, namely:(1) present the objectives, motivation, material according to the indicators and learning objectives to the students and instructed the students to write it, then devide students into several groups, (2) distribute worksheet to the students and then provide questions to the students about material in the worksheet, 3) instruct the students to work in group to do worksheet question, (4) refers to the students based on the number of heads to present the result of the discussion and answer worksheet question, (5) asking the students to conclude that the material has been studied. The implementation of the cooperative of NHT learning model can improve student learning activite and the learning outcomes of students in class Xc SMAN 1 Bungin.